TERRORISM, INTERNATIONAL MIGRATION AND BORDER CONTROL - Cinoglu, Huseyin (European Scientific Journal, ESJ, 2013)
In this article the relationship between migration and terrorism will be scrutinized. This study revealed that to deal with the situations that create social crises and public unrest such as terrorist attacks, governments are generally inclined to adopt heavy security policies, which usually include force. Public expectations and public pressure play an important role on this inclination. The study also proved that security based policies usually satisfy the expectations of the masses, but the same policies raises anxiety and fear for the immigrants and foreigners who live in that particular country. Since these tight security applications have been frequently encountered in the USA and EU after large scale terrorist attacks, this article will focus on these two countries.﻿﻿